19th International Conference on Finite Elements in Flow Problems. (30th January 2019) - van Brummelen, Harald; Corsini, Alessandro; Perotto, Simona; Rozza, Gianluigi
Abstract: This special issue presents contributions from the semi-plenary lecturers of the Nineteenth International Conference on Finite Elements in Flow Problems held in Rome, Italy, on 5–7 April 2017. The papers provide an overview of the current developments in the vanguard of finite-element methods in fluid dynamics and related areas, and cover a wide range of techniques, including model reduction, cut and immersed-boundary methods, space-time methods and isogeometric analysis, with applications spanning fluid-solid interaction, biology and biomechanics, and multi-phase flows.